2022
DOI: 10.1007/s00018-022-04593-8
|View full text |Cite|
|
Sign up to set email alerts
|

Functional interdependence of the actin regulators CAP1 and cofilin1 in control of dendritic spine morphology

Abstract: The vast majority of excitatory synapses are formed on small dendritic protrusions termed dendritic spines. Dendritic spines vary in size and density that are crucial determinants of excitatory synaptic transmission. Aberrations in spine morphogenesis can compromise brain function and have been associated with neuropsychiatric disorders. Actin filaments (F-actin) are the major structural component of dendritic spines, and therefore, actin-binding proteins (ABP) that control F-actin dis-/assembly moved into the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…Studies from us and others identified cofilin1 and ADF (also known as destrin, encoded by Dstn ) as key actin regulators in neurons ( 39 , 40 ), whose inactivation shifted the actin equilibrium toward F-actin ( 20 , 22 , 23 ). Further, we recently demonstrated an interaction of cofilin1 with both CAP1 and CAP2 in neurons ( 33 35 ). We therefore expected increased SRF activity in neurons lacking (i) cofilin1, (ii) cofilin1 and ADF, (iii) CAP1, and/or (iv) CAP2.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Studies from us and others identified cofilin1 and ADF (also known as destrin, encoded by Dstn ) as key actin regulators in neurons ( 39 , 40 ), whose inactivation shifted the actin equilibrium toward F-actin ( 20 , 22 , 23 ). Further, we recently demonstrated an interaction of cofilin1 with both CAP1 and CAP2 in neurons ( 33 35 ). We therefore expected increased SRF activity in neurons lacking (i) cofilin1, (ii) cofilin1 and ADF, (iii) CAP1, and/or (iv) CAP2.…”
Section: Resultsmentioning
confidence: 90%
“…Because previous studies revealed a cooperation of cofilin1 and CAP1 in actin subunit dissociation and in neuron morphology ( 31 , 33 , 35 , 41 ), we tested whether compound inactivation of both ABPs further increased SRF activity. CRE-expressing Cfl1 flx/flx / Cap1 flx/flx neurons (Cfl1/CAP1-dKO) displayed an increase in SRF reporter activity very similar to that in CAP1-KO neurons (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…pcDNA3.1-CAP1-eGFP was purchased from GenScript, where CDS of NM_007598.4 was cloned upstream of eGFP. mCherry-CAP1, MYC-CAP1 and corresponding constructs with point mutations have been described previously (Heinze et al, 2022).…”
Section: Dna Constructs and Oligonucleotidesmentioning
confidence: 99%
“…Instead, SRF activity was strongly increased upon inactivation of cyclase-associated protein 1 (CAP1), but not of its homolog CAP2. CAP1 is an ABP with largely unknown physiological functions (Rust et al, 2020; Rust and Marcello, 2022), which has been implicated in neuronal actin regulation only recently (Schneider et al, 2021b; Heinze et al, 2022). Reporter assays in isolated neurons combined with confocal microscopy as well as pharmacological and genetic approaches revealed that CAP1 promotes cytosolic MRTF retention and represses MRTF-SRF-induced gene expression via an actin-dependent mechanism.…”
Section: Introductionmentioning
confidence: 99%